Host adaption to the bacteriophage carrier state of Campylobacter jejuni - Brathwaite, Kelly J.; Siringan, Patcharin; Connerton, Phillippa L.; Connerton, Ian F. (Elsevier, 2015)
The carrier state of the foodborne pathogen Campylobacter jejuni represents an alternative life cycle whereby virulent bacteriophage can persistent in association with host bacteria without commitment to lysogeny. Host bacteria exhibit significant phenotypic changes that improve their ability to survive extra-intestinal environments but exhibit growth phase dependent impairment in motility. We demonstrate that early-exponential phase cultures become synchronised with respect to the non-motile phenotype, which corresponds with a reduction in their ability adhere and invade intestinal epithelial cells. Comparative transcriptome analyses (RNA-seq) identify changes in gene expression that account for the observed phenotypes: down regulation of stress response genes hrcA, hspR and perR; and down regulation of the major flagellin flaA with the chemotactic response signalling genes cheV, cheA and cheW. These changes present mechanisms by which the host and bacteriophage can remain associated without lysis, and the cultures survive extra-intestinal transit. These data provide a basis for understanding a critical link in the ecology of Campylobacter bacteriophage.